Penerapan Budidaya Ikan Lele Sistem Bioflok pada BUMDes Bumi Paccelekang Sejahtera di Desa Paccelekang Kabupaten Gowa Sulawesi Selatan: The Implementation System of Biofloc Catfish Farming at BUMDes Bumi Paccelekang Sejahtera in Paccelekang Village, Gowa Regency, South Sulawesi - Jayadi, Jayadi; Rosada, Ida; Nursyahran, Nursyahran; Hamdillah, Andi; Hasri, Hasri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Pattallassang District is a Mamminasata Metropolitan development area for urban settlements with an area of 5,983 Ha as an eastern Satellite City in Panaikang Village and Paccelekang Village, Pattallassang District. To improve the welfare of the people of Pacellekang Village, BUMDes Bumi Paccellekang Sejahtera (BUMDes BPS) was established, an agro-complex-based integrated tourist destination program. This Community Service activity aims to introduce innovative biofloc technology for catfish farming and provide technical guidance to catfish farming groups in Paccelekang Village through the biofloc system. The Community Service Program (PKM) was conducted in September 2024 in Paccelekang Village, targeting members of the BUMDes Paccelekang Sejahtera catfish farming group. The approach model used in this PKM program is Participatory Rural Appraisal (PRA). The results of the PKM activities, through counseling and training programs, show that on average, partners had a low level of knowledge and skills regarding biofloc catfish farming techniques, with 70% (21 members) categorized as low, and only 10% (3 members) and 20% (6 members) categorized as good and fair, respectively. However, after the counseling and training, the knowledge level of the partners improved, with 10% (3 members) still in the low category, and 10% (3 members) and 80% (24 members) now categorized as good and fair, respectively. Quantitatively, there was a significant improvement in partner knowledge after the counseling and training. Continuous assistance will be provided until the partners become proficient in managing and cultivating catfish using the biofloc system.